SYNTHESIS AND SOME CHEMICAL TRANSFORMATIONS OF NEW FUNCTIONALIZED 2-IMINO-2,5-DIHIDROFURAN (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
New functionalized 2-imino-2,5-dihydrofuran has been synthesized by inter-action of 3-hydroxy-3-methylbutane-2-one with phenylhydrazide of cyanoacetic acid. Some chemical transformations have been carried out.
Keywords: 2-imino-2,5-dihydrofuran; 3-hydroxy-3-methylbutane-2-one; phenylhydrazide; cyanoacetic acid